Analytical and Functional Determination of Polymyxin B Protein Binding in Serum - Abodakpi, Henrietta (Antimicrob Agents Chemother, 2015)
To enhance our understanding of the pharmacological properties of polymyxin B, serum protein binding for polymyxin B1, B2, and B3 and for isoleucine-polymyxin B1 was evaluated. Using equilibrium dialysis and ultrafiltration, comparable protein binding was found in all 4 components of polymyxin B (92% to 99%). Protein binding in human serum was further assessed using a functional assay, the results of which were in general agreement with previous findings (approximately 90%).